Educating applied arts and design students on bamboo crafts through educational trip and studio project - Kamaruddin, Zumahiran; Ab Jalil, Nurlelawati; Abdul Rahman, Julaila (Zes Rokman Resources, 2017)
This paper aims to elaborate on how the educational trip can enhance the teaching and learning in the enterprise of bamboo craft as reflected in the studio project approach of Applied Arts and Design Studio. The rationale is that an educational trip to related places for inputs and exposure to the students before their involvement in the design process in the studio is crucial. The visit gives awareness and knowledge to the students on the bamboo craft and its production process. Craft is traditionally associated with the making of objects that requires manual skill, dexterity, and experience while its production is to exercise skill based on knowledge. Therefore, this paper sets out how the educational trip is relevant in the context of studio-based teaching and learning on the bamboo craft project for the students of Applied Arts and Design programme. The emphasis of this paper is on how educational trip is important for the students, namely experiencing a new environment, acquiring new insights and going through informal learning environment. Bamboo craft is bound to the understanding of production method, sensibilities of materials and handling of techniques during production. Understanding of the process would be fruitfully achieved through direct observation at the field work apart from doing background research. This approach to teaching and learning in the field of applied arts and design is relatively novel and essential for successful outcomes of the studio project. Accordingly, the outcome and contribution of this paper is a better understanding of the role of an educational trip in enriching the teaching and learning process for the studio-based subject which focuses on craft production.